Health transition in Africa: practical policy proposals for primary care - D Maher; L Smeeth; J Sekajugo (The World Health Organization, 2010)
Sub-Saharan Africa is undergoing health transition as increased globalization and accompanying urbanization are causing a double burden of communicable and noncommunicable diseases. Rates of communicable diseases such as HIV/AIDS, tuberculosis and malaria in Africa are the highest in the world. The impact of noncommunicable diseases is also increasing. For example, age-standardized mortality from cardiovascular disease may be up to three times higher in some African than in some European countries. As the entry point into the health service for most people, primary care plays a key role in delivering communicable disease prevention and care interventions. This role could be extended to focus on noncommunicable diseases as well, within the context of efforts to strengthen health systems by improving primary-care delivery. We put forward practical policy proposals to improve the primary-care response to the problems posed by health transition: (i) improving data on communicable and noncommunicable diseases; (ii) implementing a structured approach to the improved delivery of primary care; (iii) putting the spotlight on quality of clinical care; (iv) aligning the response to health transition with health system strengthening; and (v) capitalizing on a favourable global policy environment. Although these proposals are aimed at primary care in sub-Saharan Africa, they may well be relevant to other regions also facing the challenges of health transition. Implementing these proposals requires action by national and international alliances in mobilizing the necessary investments for improved health of people in developing countries in Africa undergoing health transition.